Factors Affecting Foreign Exchange Reserves in Indonesia Year 2020-2022 - Nabila Ananda Putri Harahap; Nurul Jannah; Budi Dharma (Yayasan Riset dan Pengembangan Intelektual, 2023)
This study aims to determine the factors that affect foreign exchange reserves in Indonesia in 2020-2022. Foreign exchange reserves are external assets that can be directly available to and are under the control of the Central Bank as the monetary authority to finance balance of payments imbalances, intervene in the market in order to maintain exchange rate stability, and other purposes. Foreign exchange reserves are influenced by many interrelated factors, including exports and the rupiah exchange rate. This research method is quantitative, data processing using SPSS and tests with multiple linear regression. The type of data used in this study is secondary data obtained from the Central Bureau of Statistics and Bank Indonesia with time series data for 3 years on a monthly basis (January to December). The data analysis used is multiple linear analysis and classical assumption test. The results showed that the Inflation Rate had an effect and was not significant to Indonesia's foreign exchange reserves. Interest rates have a positive and significant effect on Indonesia's foreign exchange reserves. The exchange rate has an effect and is not significant to Indonesia's foreign exchange reserves. Foreign Debt has a positive and significant effect on Indonesia's foreign exchange reserves. This shows that the stronger the Foreign Debt in Indonesia, the more it will affect the foreign exchange reserves in the country of Indonesia.